Pengaruh penggunaan TikTok Terhadap Nilai Self-Admiration pada Generasi Z di Era Digital - Halimah As-Sa’diah; Sofiyana Habibah; Laras Isa Ningsih; istiqomah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Abstract Self-Amiration is defined as a feeling of admiration or respect for oneself. Excessive SelfAdmiration can turn into narcissism or egoism, which often appears among Generation Z on various social media platforms such as TikTok. This study aims to analyze the effect of using TikTok on self-admiration among Generation Z in the digital age, the case study conducted is in a pesantren-based university environment, especially for female students of Darussalam Gontor University. The study used quantitative methods with purposive sampling techniques, involving 102 respondents with subject criteria, namely, generation Z Tiktok users with an age range of 18-26 years. The analysis technique used with the data normality test, because the results were normally distributed, the researchers conducted an independent sample t-test to compare the effect of admiration value on tiktokers and non tiktokers. The results showed that there was a significant difference in the average self-admiration value between tiktokers and non-tiktokers, it was concluded that tiktokers respondents had a higher self-admiration value than non-tiktokers with an average difference of 6.994. Keywords: TikTok, Self-Admiration, Generation Z, Social Media.